High-resolution Observations of an X6.4 Solar Flare in the Mid-infrared - Xu Yang; Wenda Cao; Meiqi Wang; Don Jennings; Jiong Qiu; Wen He; Solomon M. Perriyil; Vasyl Yurchyshyn; Lyndsay Fletcher; Paulo J. A. Simões; Murzy Jhabvala; Allen Lunsford; et al. (The Astrophysical Journal Letters)
We present a unique observation of the X6.4-class flare SOL2024-02-22T22:34 using the Mid-InfraRed Imager (MIRI) at the Goode Solar Telescope. Three ribbon-like flare sources and one unidentified source were detected in MIRI’s two mid-infrared (mid-IR) bands at 5.2 and 8.2 μ m. The two stronger ribbons displayed maximum mid-IR enhancements of 21% and 18% above quiet-Sun levels and 10% in Helioseismic and Magnetic Imager (HMI) continuum intensity ( I _c ). The weak ribbon and the unidentified source had maximum mid-IR enhancements of 7% but showed HMI/ I _c dimmings, instead of excess emissions. Our result suggests that mid-IR emission forms in a higher layer during the flare and is more sensitive to flare heating than HMI/ I _c emission. The MIRI observations have high temporal resolution (2.6 s cadence in these observations) and show apparent source motions. One flare ribbon extends along weak vertical magnetic-field channels in the sunspot umbra, light bridge, and penumbra, with an approximately 30 s delay between HMI/ I _c and 8.2 μ m emissions. Meanwhile, the unidentified source moved at an apparent speed of 130 km s ^−1 from a mixed-polarity area to one flare ribbon with a strong HMI/ I _c enhancement. We studied available hard X-ray/microwave imaging spectroscopy and used nonlinear force-free field extrapolation modeling to identify flare structures. The observational evidence strongly favors the chromospheric origin of the unidentified mid-IR source. Comparison with the X1.0 flare SOL2022-10-02T20:25 indicates that the total amount of high-energy electron (>60 keV) flux density is a key factor in determining the total brightening area and the maximum intensity enhancement in HMI/ I _c emissions.